EGMR 40575/10_67474/10 vom 2. Oktober 2018 , CASE OF MUTU AND PECHSTEIN v. SWITZERLAND - Hudoc Ch (2018)
Remainder inadmissible (Art. 35) Admissibility criteria;(Art. 35-3-a) Ratione personae;No violation of Article 6 - Right to a fair trial (Article 6 - Civil proceedings;Disciplinary proceedings;Article 6-1 - Impartial tribunal;Independent tribunal);Violation of Article 6 - Right to a fair trial (Article 6 - Civil proceedings;Disciplinary proceedings;Article 6-1 - Public hearing);Pecuniary damage - claim dismissed (Article 41 - Pecuniary damage;Just satisfaction);Non-pecuniary damage - award (Article 41 - Non-pecuniary damage;Just satisfaction); Violation: 6;6-1; No violation: 6;6-1